Proses Terbentuknya Asas Praduga Terhadap Politik Dinasti Suatu Negara - Ismail, Alferin Salsabilla (AL WASATH Jurnal Ilmu Hukum, 2023)
this article discusses the phenomenon of dynastic politics in Indonesia and its impact.By using this type of literature study research or literature studyBy using this type of literature study research or literature study.Dynastic politics is political power that is exercised by a handful/group of people who have family ties either by blood or marriage. Dynastic politics is political power that is exercised by a handful/group of people who have family ties either by blood or marriage. The results of this study indicate that the proliferation of dynastic politics in a country is due to network strength, financial strength, the role of political parties and there are no laws and regulations governing dynastic politicsThe results of this study indicate that the proliferation of dynastic politics in a country is due to network strength, financial strength, the role of political parties and there are no laws and regulations governing dynastic politics.The impact that arises from dynastic politics is that law enforcement does not work, or stutters when political interests collide or the cases it handles come into direct contact with the political forces in power, besides that it closes opportunities for people who are reliable and qualified cadres, and the function of controlling power is weakened and does not work effectively so that there is a possibility of deviations of power such as corruption, collusion and nepotism.The impact that arises from dynastic politics is that law enforcement does not work, or stutters when political interests collide or the cases it handles come into direct contact with the political forces in power, besides that it closes opportunities for people who are reliable and qualified cadres, and the function of controlling power is weakened and does not work effectively so that there is a possibility of deviations of power such as corruption, collusion and nepotism.